Possible involvement of microtubule disruption in bipolar budding of a Sendai virus mutant, F1-R, in epithelial MDCK cells. - Tashiro, M (1993)
Envelope glycoproteins F and HN of wild-type Sendai virus are transported to the apical plasma membrane domain of polarized epithelial MDCK cells, where budding of progeny virus occurs. On the other hand, a pantropic mutant, F1-R, buds bipolarly at both the apical and basolateral domains, and the viral glycoproteins have also been shown to be transported to both of these domains (M. Tashiro, M. Yamakawa, K. Tobita, H.-D. Klenk, R. Rott, and J.T. Seto, J. Virol. 64:4672-4677, 1990). MDCK cells were infected with wild-type virus and treated with the microtubule-depolymerizing drugs colchicine and nocodazole. Budding of the virus and surface expression of the glycoproteins were found to occur in a nonpolarized fashion similar to that found in cells infected with F1-R. In uninfected cells, the drugs were shown to interfere with apical transport of a secretory cellular glycoprotein, gp80, and basolateral uptake of [35S]methionine as well as to disrupt microtubule structure, indicating that cellular polarity of MDCK cells depends on the presence of intact microtubules. Infection by the F1-R mutant partially affected the transport of gp80, uptake of [35S]methionine, and the microtubule network, whereas wild-type virus had a marginal effect. These results suggest that apical transport of the glycoproteins of wild-type Sendai virus in MDCK cells depends on intact microtubules and that bipolar budding by F1-R is possibly due, at least in part, to the disruption of microtubules. Nucleotide sequence analyses of the viral genes suggest that the mutated M protein of F1-R might be involved in the alteration of microtubules.